2013
DOI: 10.1111/jmi.12009
|View full text |Cite
|
Sign up to set email alerts
|

Measuring three‐dimensional strain distribution in tendon

Abstract: SummaryTendons are tough fibrous tissues that facilitate skeletal movement by transferring muscular force to bone. Studies into the effects of mechanical stress on tendons have shown that these can either accelerate healing or cause tendon injuries depending on the load applied. It is known that local strain magnitude and direction play an important role in tendon remodelling and also failure, and different techniques to study strain distribution have been proposed. Image registration and processing techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…T. Thorpe, Klemt, et al 2013). Fascicles exhibit a helical organization within the whole tendon structure as well (Kalson et al 2012; Kannus 2000; Khodabakhshi et al 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. Thorpe, Klemt, et al 2013). Fascicles exhibit a helical organization within the whole tendon structure as well (Kalson et al 2012; Kannus 2000; Khodabakhshi et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Thorpe et al 2012). Fiber sliding is also shown as a dominant mechanism of motion during tendon stretch (Khodabakhshi et al 2013; Li et al 2013), particularly in more energy storing, flexor tendons of porcine (Screen, Toorani, and Shelton 2013) and primarily positional, extensor tendons of equine (C. T. Thorpe, Klemt, et al 2013) where it has been demonstrated that more fiber sliding occurs than their positional or energy storing counterparts, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This global DVC (Dall' Ara et al, 2014) consists in computing the displacement map by using the Sheffield Image Registration Toolkit (ShIRT) (Barber and Hose, 2005;Barber et al, 2007;Khodabakhshi et al, 2013). With BoneDVC, a grid with selectable nodal spacing (NS, or subvolume, or grid size) is superimposed to the images to be registered.…”
Section: Bonedvc (Previously Known As Shirt-fe)mentioning
confidence: 99%
“…Disadvantages of current DIC methodologies applied to biological tissues include the requirement for a high-resolution dot pattern, "noisy" data owing to errors in automated dot mapping, and the limitation of producing 2D/pseudo-3D analyses. Adaptations of DIC-like methodologies to biological tissues include the use of fluorescent-labeled cells instead of preplaced dots as the mapped entity (27).…”
mentioning
confidence: 99%